Pengaruh Kerjasama Orangtua Dan Guru Terhadap Perkembangan Sosial Emosionalanak pada Kelompok B di Raudhatul Athfal Al-Muhajirin Nongsa Kota Batam (Prosiding Keislaman dan Sains, 2025)
The purpose of this study is to determine whether the relationship between cooperation between parents and teachers can affect social emotional development in early childhood, especially in group B children aged 5-6 years. Given the cooperation that exists between parents and teachers will greatly affect the positive social emotional development of children. This research uses a quantitative approach. Data obtained from questionnaires. Instruments in the study need to go through an instrument trial to find out the Validation Test, Reliability Test, Classical Assumption Test (Normality Test, Multicolonearity Test and Heteroscedasticity Test) and Significance Test (T Test). Then the data is analyzed using Multiple Linear Regression analysis, Determination Analysis and Correlation Analysis. The results obtained showed that there was an influence between the cooperation of parents and teachers on the social emotional development of group B children at RA Al-Muhajirin Nongsa. From the results of the above analysis, it can be concluded that the independent variable, namely parent and teacher cooperation (X), has a significant and simultaneous effect on the dependent variable, namely social emotional development. This can be seen from the significant value of X1 (0.000 ttable (1.671). This means that 70% can be explained by the independent variable, namely parent and teacher cooperation (X). While the remaining 30% can be explained by other independent variables that are not included in this study. The conclusion in this study is that the cooperation of parents and teachers has a simultaneous and significant effect on the social-emotional development of group B children aged 5-6 years at RA Al-Muhajirin Nongsa Batam. And the next hope is that there is renewal of information or the latest findings in a field that is in line with this journal.
Keywords: Parent and Teacher Cooperation; Sosial Emotional; Development; Early Childhood